Scalp block for postoperative pain after craniotomy: A meta-analysis of randomized control trials - Chen, Yanting; Ni, Jianqiang; Li, Xiang; Zhou, Jialei; Chen, Gang (Frontiers in Surgery, 2022)
Background: Postoperative pain after craniotomy is an important clinical concern because it might lead to brain hyperemia and elevated intracranial pressure. Considering the side effects of opioid, several studies have been conducted to investigate the effect of local anesthetics, especially the scalp block, on postoperative pain. However, the strength of evidence supporting this practice for postoperative pain after craniotomy was unclear and the best occasion of scalp block was also not identified. Therefore, we conducted a meta-analysis to evaluate the efficacy, safety, and the best occasion of scalp block for postoperative pain after craniotomy. Methods: PubMed, Embase, and the Cochrane Library databases from database inception to October 10, 2021 were searched for all randomized controlled trials evaluating the effect of scalp block on postoperative pain after craniotomy. Data were assessed by StataMP 16 software. Results: A total of 12 studies were included. A random-effect model was used to analyze all data. Patients under scalp block earned fewer scores than the non-scalp block group in visual analogue scale at the very early period (MD = -1.97, 95% CI = -3.07 to -0.88), early period (MD = -1.84, 95% CI = -2.95 to -0.73) and intermediate period (MD = -1.16, 95% CI = -1.84 to -0.49). Scalp block could also significantly prolong the time of the first request of rescue analgesia and reduce the use of additional analgesics without a significant difference in the incidence of complications. Subgroup analysis showed there was no significant difference in analgesia effect between pre-incision scalp block and post-incision scalp block in all periods. Conclusion: Scalp block could lead to lower pain intensity scores, more time of the first request of rescue analgesia, and fewer analgesic drugs applied in the first 12h after craniotomy. There was no significant difference between pre-incision and post-incision scalp block in the occurrence and severity of postoperative pain.